Science and religion: Competing ways of knowing? - Webb, Mark Owen (ҚазҰУ хабаршысы. Философия, саясаттану және Мәдениеттану, 2018)
It is a commonplace in contemporary theory of knowledge that human beings avail themselves of many different ways to acquire knowledge. Our senses provide one avenue, memory another, reasoning yet another, and so on. Most of these avenues of knowledge are windows on the world; that is, they all provide information about the spatio-temporal world we all inhabit.